1980
DOI: 10.1002/art.1780231206
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing spondylitis in african blacks

Abstract: Over a period of 4 years in a large African teaching hospital, only 8 patients with ankylosing spondylitis were seen. This small number supports the impression that the disease is rare in African blacks. Patients tended to be relatively old and to have severe disease. None had iritis or a positive family history. The HLAB27 antigen was found in found in only 1 patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 15 publications
1
8
2
Order By: Relevance
“…Chalmers et al [2] reported a series of eight AS patients seen over 4 years at a large South African teaching hospital, noting that only one was HLA-B27 positive and that “the patients reported in this study appeared to have disease of unusual severity,” although admitting that selection bias may have influenced this. Ouédraogo et al [7] observed 13 cases of AS in 2 years of rheumatologic practice among 1439 patients (0.9%) from Burkina Faso, finding a 55% frequency of HLA-B27.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Chalmers et al [2] reported a series of eight AS patients seen over 4 years at a large South African teaching hospital, noting that only one was HLA-B27 positive and that “the patients reported in this study appeared to have disease of unusual severity,” although admitting that selection bias may have influenced this. Ouédraogo et al [7] observed 13 cases of AS in 2 years of rheumatologic practice among 1439 patients (0.9%) from Burkina Faso, finding a 55% frequency of HLA-B27.…”
Section: Discussionmentioning
confidence: 91%
“…In part, this has been attributed to the lower frequency of HLA-B27 in Blacks both in the US and in most but not all African ethnic groups [3, 5, 6] and, in Latinos, in the US [6], although the only study to examine the frequency of AxSpA in Mexican-Americans residing in the US showed similar frequency as Whites (1.5%) [4]. However, an early study of Black AS patients from the US and another from Burkina Faso showed the frequency of HLA-B27 in AS to range between 50 and 60% [5, 7], and other studies in Africa found even lower frequencies [2] compared to up to 90% of White patients [8]. Furthermore, in Whites, HLA-B27 positivity was associated with earlier age at disease onset, higher rates of anterior uveitis, a shorter delay to diagnosis from first symptoms, and an increased familial incidence of AS in Black and white patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…None had iritis or a positive family history. The HLA-B27 antigen was found in only one patient 16. Another study, done in Gambia, found that the risk of developing AS is small, even in HLA-B27 positive Gambians, compared to those of HLA-B27 positive Caucasians, suggesting that there may be a non-B27 protective factor reducing the prevalence of AS in this (sub) population 17…”
Section: Epidemiologymentioning
confidence: 88%
“…Older studies from Africa reported AS to be rare, with a very low frequency of HLA-B27 in patients with AS 6 7. This was attributed, as least in part, to a ‘protective’ West African B27 subtype ( B*27:03 ),7 although subsequent studies reported an association of this subtype with AS in Africans 8.…”
Section: Role Of Hla-b27mentioning
confidence: 99%